Everything everywhere all at once: mapping lay beliefs about self-control - Li, Jinyao; Gillebaart, Marleen; van Timmeren, Tim; de Ridder, Denise (Frontiers in Psychology, 2025)
IntroductionSelf-control is essential for achieving long-term goals and is influenced by individuals’ beliefs about it. Previous studies have found that those who view self-control as non-limited perform better in cognitive tasks, resist temptations more effectively, and achieve better outcomes. Understanding these beliefs is therefore crucial for fostering stronger self-control, yet a systematic understanding remains lacking.MethodsTo comprehensively map these beliefs, participants from the United States, the Netherlands, and China (total N = 150) were directly asked about their views on self-control.ResultsBy analyzing these responses, we identified 14 key components of self-control beliefs. These beliefs highlight the challenging, committed, and disciplined nature of self-control, offering a broader perspective beyond the traditional view of self-control as a limited resource.DiscussionFindings provide a comprehensive framework for understanding lay beliefs about self-control and underscore their significance in shaping self-control exertion.